Respuesta :

Answer:

Calculate P(1)

Step-by-step explanation:

Given

P(x)

[tex]Divisor = x - 1[/tex]

Required

How to determine the remainder

First, you equate the divisor to 0 to solve for x

i.e.

[tex]x - 1 = 0[/tex]

[tex]x = 1[/tex]

Next, substitute 1 for x in P(x)

Then solve for P(1)

Take for instance;

If

[tex]P(x) = x^3 - x^2 - 1[/tex]

Substitute 1 for x

[tex]P(1) = 1^3 - 1^2 - 1[/tex]

[tex]P(1) = 1 - 1 - 1[/tex]

[tex]P(1) = - 1[/tex]

Hence, the remainder is -1

ACCESS MORE